A Formula for n-times Integrated Semigroups $\boldsymbol{(\boldsymbol n\boldsymbol\in \mathbb N)}$ - Vugdalić, Ramiz (Sarajevo Journal of Mathematics, 2024)
Motivated with Hille's first exponential formula for $C_{0}$ semigroups, we prove a formula for $n-$times integrated semigroups. At first we prove a formula for twice integrated semigroup, and, later, we generalize this formula for $n-$times integrated semigroups. 2000 Mathematics Subject Classification. 47D60, 47D62